Practice visits as a tool in quality improvement: mutual visits and feedback by peers compared with visits and feedback by non-physician observers. Issue 3 (1st September 1999) - van den Hombergh, P; Grol, R; van den Hoogen, H J; van den Bosch, W J
Abstract : OBJECTIVE: To evaluate and compare the effects of two programmes of assessment of practice management in a practice visit: mutual visits and feedback by peers compared with visits and feedback by non-physician observers. DESIGN: Prospective, randomised intervention study, with follow up after one year. SETTING: General practices in the Netherlands in 1993 and 1994. SUBJECTS: A total of 90 general practitioners (GPs) in 68 practices; follow up after one year comprised 81 GPs in 62 practices. MAIN MEASURES: Scores on indicators and dimensions of practice management in the visit instrument to assess practice management and organisation (a validated Dutch method to assess practice management in a practice visit). Change was defined as the difference in score between the first visit and the visit after one year on 208 indicators and on 33 dimensions of practice management. RESULTS: Data of 44 mutual visits by peers were compared with data of 46 visits by non-physician observers. After a year both programmes showed improvements on many aspects of practice management, but different aspects changed in each of the two programmes. After mutual practice visits, GPs scored significantly higher on content of the doctor's bag, on collaboration with colleagues, on collaboration with other care providers, and on accessibility of patient information than after a visit by a non-physician observer. The visits by non-physician observers resulted in a higher score on extent of use of records and on assessment on outcome and year report. CONCLUSION: Change after mutual practice visits and feedback by peers is more marked than after a visit and feedback by a non-physician observer.